PENILAIAN STATUS KEBUGARAN ANAK SEKOLAH DASAR DURI KEPA 11 JAKARTA BARAT - Kuswari, Mury (Universitas Esa Unggul, 2016)
AbstractSchool-age children act as an investment for the nation, since they are the future generation. The optimal Growth and developmentÂ of school-age children depends on adequate nutrient intake through high quality food and their physical fitness. For a school age children, physical fitness status is very important to suppport learning and playing activity. Children who are at good physical fitness status will be able to learn, play, or doing other activities longer than those who did not have optimal physical fitness status. Physical fitness status influenced by several things, including nutrient intake and body composition. This activity aims to assess the fitness status of male and female students of State Elementary School Duri Kepa 11. This activity is done with cross-sectional design. This activities carried out in March 2016. The population in this activity are children of school age grade 3 and 4 in Duri Kepa SD Negeri Jakarta, 83 students were present and willing to become respondent in this activity.Â Fitness status measurement is done by bleep test method and then the result compared with the fitness status standard. Based on the measurement, results showed thatÂ majority of female students atÂ SDN Duri Kepa 11 status is not fit, yet, most of the male students were on optimal physical fitness status.Â Constant monitoring of elementary school studentâ physical fitness status need to be done not only to support childrens health status but also as a basis to do an health intervention. Â Keywords: fitness, student, elementary schoolÂ AbstrakAnak usia sekolah adalah investasi bangsa, karena mereka adalah generasi penerus bangsa. Tumbuh berkembangnya anak usia sekolah yang optimal tergantung pemberian asupan zat gizi dengan kualitas dan kuantitas yang baik serta benar. Bagi seorang anak, kebugaran sangat penting terutama sebagai modal utama dalam melaksanakan kegiatan belajar dan bermain. Anak yang bugar akan memiliki rentang perhatian lebih lama dalam belajar, bermain, atau berbagai kegiatan lainnya. Kebugaran jasmani dipengaruhi oleh beberapa hal, diantaranya asupan zat gizi dan komposisi tubuh. Kegiatan ini bertujuan untuk menilai status kebugaran siswa dan siswi SDN Negeri Duri Kepa 11. Kegiatan ini dilakukan dengan desain cross-sectional. Waktu kegiatan dilakukan pada bulan Maret 2016. Populasi dalam kegiatan ini adalah anak-anak usia sekolah kelas 3 dan 4 di SD Negeri Duri Kepa Jakarta. Dari jumlah populasi yang ada, didapatkan besar sampel yang hadir dan bersedia untuk menjadi responden sebesar 83 siswa/i. Pengukuran status kebugaran dilakukan dengan cara bleep test dan kemudian dibandingkan dengan standar kebugaran anak. Berdasarkan hasil pengukuran didapatkan hasil sebagian besar siswi SDN Duri Kepa 11 berstatus tidak bugar namun, sebagian besar siswa SDN Duri Kepa Berstatus Bugar. Banyaknya siswi yang berstatus tidak bugar, pemantauan terhadap kebugaran dan pembinaan kebugaran jasmani siswa SD perlu dilakukan untuk menunjang status kesehatan anak sekolah.Kata Kunci: kebugaran, siswa, sekolah dasar